Interview with Noam Chomsky (Papeles, 2013)
Our comments for prof. Chomsky before this interview: Science today is acontroversial issue from different point of view: One, because industrial andfinancial scopes of science are its development focus. Then, social sciences no alwayscould bring profits as we get in other fields. Other thing, maybe the most interestingfor us, and maybe linked with our word above is (specially after postmodernismtendencies), the method of social sciences, its prestigious and outcomes have manyhermeneutics problems that (apparently) natural and formal sciences do not have.I think postmodernism stream of thought confused us in many cases more thanthe light that they shade on social problems. And finally, we need to evaluate howis the current contribution of some social sciences as economics and linguistics(and other) to criticize and build a better human being, from what kind of scientificrigor, because postmodernism brought the idea that all the border are broken andall limited too, then now we have the dictatorship of the particular true all thetime. And, universal are desired for scientific and academic thought, in good wayof course: Universals without absolutes.